PENDAMPINGAN PRAKTEK IBADAH DALAM PESANTREN KILAT DI MTS SUNAN AMPEL DI DUKUH WATU AGUNG DESA DAYAKAN KECAMATAN BADEGAN PONOROGO - Widodo (Journal of Islamic Science Community, 2022)
In the community service program carried out by students of the Riyadlotul Mujahidin Islamic Institute at MTs Sunan Ampel, namely conditioning the entire design of Islamic boarding school activities with the aim of accompanying daily worship and providing understanding to students regarding religious material, especially recitation and fiqh. The method used in the mentoring is the lecture method and direct worship practice. The accuracy of the selection of methods greatly affects the level of success of a goal in mentoring. The assistance provided can motivate students to learn about religion and get used to worship activities every day, as evidenced by the very high response to this lightning boarding school activity. The implementation of community service activities (PKM) is running effectively and in accordance with what is expected.